Embedding owner-manager values in the small and medium sized enterprise context: a Lockean conceptualisation - Oldham, Simon (Journal of business ethics, 2024)
The salience of owner-manager values to small and medium sized enterprise (SME) engagement with ethics and social responsibility is well documented. Despite this, understanding of how these values are transposed into and become embedded within the culture, norms and practices of SMEs remains limited. Through drawing on a sample of SMEs in the South West of England, this paper identifies the mechanisms which owner-managers seek to use to embed their values within their organisations—rational values sharing, affective values sharing and building values-aligned relationships—while distinguishing a number of barriers they meet in the process. It further builds on previous research and explicates such embedding processes by means of discerning and providing rich descriptions of eight key owner-manager values. The work of Alain Locke on values is drawn on theoretically to frame the embedding of such values as a reflexive, ongoing process, while the utility of his work—largely absent from the field of business ethics so far—is highlighted.